Analisis Pengaruh Mutasi, Dan Promosi Jabatan Terhadap Pengembangan Karir Pegawai Di Manado - -, Dasplin (JURNAL RISET BISNIS DAN MANAJEMEN, 2014)
The purpose of this study was to determine the effect of the mutation, and the promotion of the employee's career development. Data collection methods used in this study is a questionnaire with a population of 70 career employees and all the research sample. Data analysis method used is the method of multiple regression analysis. The results showed that the mutation, and the promotion of positive significant effect on employee career development is carried out in North Sulawesi Prosecutor's Office is able to provide positive things for employees such as increase knowledge and experience, facilitating employees to strengthen the relationship fellow co-workers. Keywords: transfer, promotion, career development employee